Pengaruh Harga dan Promosi Terhadap Loyalitas Konsumen Pengguna Aplikasi Grab-Food di Yogyakarta - Zufriah, Deniyati; Sarjita, Sarjita (Jurnal Bisnis, Manajemen, dan Akuntansi, 2024)
This research aims to determine the influence of price variables and promotion variables on consumer loyalty among Grab-Food users in Yogyakarta. The variables used in this study consist of independent variables, namely price (X1) and promotion (X2), as well as the dependent variable, which is consumer loyalty (Y). The data was analyzed using descriptive analysis, instrument quality testing (validity and reliability tests), and hypothesis testing through multiple linear regression (t-test and R² test), with a total of 100 respondents. The results of the analysis using the multiple linear regression equation show that price has a significant effect on consumer loyalty among Grab-Food users in Yogyakarta. This means that price significantly influences consumer loyalty and has a simultaneous significant effect on consumer loyalty. Consumer loyalty of Grab-Food users in Yogyakarta is influenced by price (X1) and promotion (X2), while the remaining factors are influenced by other variables not included in this study.